A Mosquito Culex (Melanoconion) pilosus (Dyar and Knab) (Insecta: Diptera: Culicidae) - Diana Vork; C. Roxanne Rutledge Connelly (EDIS)
This small, dark mosquito tends to feed on reptiles and amphibians. It is found in the southeastern United States and many countries in Central America and South America. This 3-page fact sheet was written by Diana Vork and C. Roxanne Connelly, and published by the UF Department of Entomology and Nematology, April 2012.